A scoping review of policies to encourage breastfeeding, healthy eating, and physical activity among rural people and places in the United States - M. Renée Umstattd Meyer; Bailey Houghtaling; Marilyn E. Wende; Khawlah H. Kheshaifaty; Haley Delgado; Stephanie A. Eze; Cassady Mecate; Rebekah Summerall Woodward; Randa Lopez Morgan; Kathy J. Krey (BMC Public Health, 2024)
Abstract Background Rural U.S. residents experience a disproportionate burden of diet and physical activity (PA) related chronic disease compared to urban residents, due to resource and economic challenges. Diverse policy approaches for chronic disease prevention have been implemented to address barriers to breastfeeding, healthy eating, and PA. Therefore, the purpose of this paper is to describe policy supports for breastfeeding, healthy eating, and/or PA occurring in rural U.S. areas. Methods A scoping review was conducted March-June 2020 to identify policy, systems, and environment change approaches occurring in the rural U.S. for breastfeeding, healthy eating, and PA. Search procedures were guided by the PRISMA-ScR, Arksey and O’Malley’s work (2007), and a science librarian. Medline, PubMed, Web of Science, and Agricola were used to identify peer-reviewed research. ProQuest Dissertations and Theses A&I were used to identify dissertation research. Grey literature searches included Google, Google Scholar, government pages, and public health, federal nutrition assistance program, Cooperative Extension Services, and related webpages. Policy results are reported and inclusion criteria were: (1) breastfeeding, healthy eating, and/or PA focus; (2) about policy factors; (3) specific to U.S. rural populations/places; and (4) English language. Outcomes (study/source design, objective(s), methods/measurement, setting, population characteristics, behavioral focus, policy-specific results) were extracted into a standardized Excel document. Results Results include 122 total sources: original research, with some sources referencing multiple behaviors, (n = 74 sources: 8 breastfeeding, 41 healthy eating, 42 PA), grey literature (n = 45 sources: 16 breastfeeding, 15 healthy eating, 27 PA), and graduate research (n = 3 sources: 1 breastfeeding, 2 healthy eating, 1 PA). Breastfeeding policy initiatives included policies or programs at hospitals, increasing access to resources, and improving culture or norms at workplaces. Healthy eating policy initiatives included increasing access to healthy foods, reducing financial burden, implementing programs, food assistance programs, and healthy food prescriptions at healthcare facilities. PA policy initiatives focused on Complete Streets, joint or shared use efforts, Safe Routes to Schools, master plans for greenways, trails, and/or transportation, school health plans, and childcare/school standards. Conclusions Results from this scoping review compile and offer commentary on existing policy solutions to improve breastfeeding, healthy eating, and/or PA in the rural U.S.